If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 = -8X + 9X Combine like terms: -8X + 9X = 1X -35 = 1X Solving -35 = 1X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. -35 + -1X = 1X + -1X Combine like terms: 1X + -1X = 0 -35 + -1X = 0 Add '35' to each side of the equation. -35 + 35 + -1X = 0 + 35 Combine like terms: -35 + 35 = 0 0 + -1X = 0 + 35 -1X = 0 + 35 Combine like terms: 0 + 35 = 35 -1X = 35 Divide each side by '-1'. X = -35 Simplifying X = -35
| 0.002k=83 | | -2-X+6x=43 | | P-16=32 | | B/(1/3)=8/21 | | 5w^2-28=31w | | w^2+8w=60 | | 0.5c=10 | | B/(1/3) | | 36x^2+60s=-25 | | a/b=10a | | -4/11y=16/33 | | 3x^2-30x=-63 | | 7x-4x=-45 | | 48+d=60 | | 8+5ln(6x)=13 | | 36s^2+60s=60s | | 3x+4y-7x+2y= | | M-5=18 | | 8x+247+6x+185=180 | | 7x-4x=45 | | 52-n=24 | | 5r/r | | 4(3x-8)=39 | | 33+c=54 | | 0.09a=9 | | 28+b=50 | | 12m-2m=90 | | 31-x=16 | | 0.1m=5 | | m+33=20 | | A+12=25 | | 0.02f=48 |